2018
DOI: 10.1513/annalsats.201703-259oc
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Asthma in the United States, 2008–2013

Abstract: Rationale: Asthma is a chronic disease that affects quality of life, productivity at work and school, and healthcare use; and it can result in death. Measuring the current economic burden of asthma provides important information on the impact of asthma on society. This information can be used to make informed decisions about allocation of limited public health resources.Objectives: In this paper, we provide a comprehensive approach to estimating the current prevalence, medical costs, cost of absenteeism (misse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
264
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(318 citation statements)
references
References 45 publications
6
264
1
3
Order By: Relevance
“…In the USA alone, 9–10 patients with asthma die each day due to lack of effective treatment for this disease [5,6,8]. The total cost of asthma in the USA exceeded $81 billion in 2013 [9], up from $56 billion in 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA alone, 9–10 patients with asthma die each day due to lack of effective treatment for this disease [5,6,8]. The total cost of asthma in the USA exceeded $81 billion in 2013 [9], up from $56 billion in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Novel but affordable systemic and/or inhaled therapies are urgently needed in asthma, in particular for those with severe asthma, which has a disproportionate burden on healthcare costs [9,2023]. Although strides have expanded the current armamentarium of asthma therapy, pharmacologic therapies for the different phenotypes of asthma remain limited and inadequate, in particular for non-eosinophilic asthma [2426].…”
Section: Introductionmentioning
confidence: 99%
“…(Kim et al,2013). The cost of asthma for adults and children is $81.9 billion annually when considering healthcare-related expenditures and costs incurred due to absenteeism and mortality (Nurmagambetov, Kuwahara, & Garbe, 2018). Theincreased exposure to air pollution and secondhand smoke for children living in poverty lead to expensive, long-term complications.…”
Section: Three Exemplars Of Child Povertymentioning
confidence: 99%
“…Although studies have reported mixed findings [53•, 123, 181, 197], they highlight the need to revisit the widely-debated issue of the efficacy of single- versus multifaceted interventions and to improve behavioral compliance in a sustainable way. Given the clinical and economic burden of allergic diseases [199, 200], such as asthma, cost-effective interventions could have significant public health impacts.…”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%